COMPARATIVE ANTIDIABETIC ACTIVITY OF MARKETED GLICLAZIDE FORMULATION WITH GLICLAZIDE LOADED PELLETS CONTAINING GUM KONDAGOGU AS A DRUG RETARDING MATERIAL IN RATS - Jayapala Reddy, Kavitha; Krishna Mohan, Gottumukkala (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Controlled drug delivery systems significantly enhances therapeutic efficacy of drugs. Drug retarding polymers are the key performers in such designed systems. Objective: The main objective of study is to evaluate antidiabetic effect of gliclazide loaded pellets developed by green synthesis technique where in gum Kondagogu is used as natural drug retarding polymer and compared with existing Gliclazide Marketed formulation. Methods: The study is carried out in Wistar rats with body weight ranging between 100-220g. Diabetes was induced in animals by injecting alloxan 150mg/kg/bodyweight intraperitoneally (i.p.). Animals were divided into four groups. Group I - Control, Group II- Diabetic Control, Group III- Diabetic treated with Gliclazide Marketed formulation, and Group IV- Diabetic treated with gliclazide loaded pellets orally. Fasting blood glucose levels were estimated at 0, 2, 4, 6, 8, 10, 12 and 24 hours to understand the release of the drug from polymer matrix. Results: The results have shown that the on single oral administration of gliclazide loaded pellets coated with gum Kondagogu showed almost similar anti-diabetic activity when compared with marketed formulation The maximum reduction in the glucose level were observed at 4th and 6th hour and later the glucose levels were sustained in the same pattern to that of marketed formulation. Conclusion: In the present study, an effort has been made to evaluate the efficacy of gum kondagogu as a novel controlled release matrix forming material and thus it could be concluded that gum kondagogu could be a controlled release matrix polymer and be a suitable substituent to existing synthetic polymers for drug retardation in the pharmaceutical industry. KEYWORDS: Gum Kondagogu, Gliclazide, tree gum exudates, natural drug retarding material